MyPlate dietary guidelines presentation created in Microsoft PowerPoint - Busch, Felicia; Busch, Felicia; Learning Zone Express (Firm) ([Owatonna, Minn.] : Learning Zonexpress, 2011)
This 35 slide PowerPoint presentation explains the USDA's food icon and Dietary Guidelines. It includes a comparison of MyPlate and past food guides such as the food pyramid, the importance of calorie balance, foods to increase and decrease, and physical activity. Includes review questions and presenter's notes in a 35 page resource guide.
Include user guide and printed of the power point.
Power point created based on information published by the U.S. Department of Agriculture (USDA), Center for Nutrition Policy and Promotion.
System requirements: Windows or Macintosh; DVD-ROM drive and Microsoft Power Point.
Keywords: Nutrition; Diet